Intellectual Showcasing: Articulating the Thinking Behind our Practice - McGregor, Sue LT (Nurture, 2007)
The tangible products and services provided by our profession benefit society, and involve intellectual activity, especially moral judgements. If we present ourselves to the public in such a way that people are clear about why we are doing what we do, then fewer misunderstandings would abound and more valued practice would result. This paper asks us to examine the merits of clearly articulating the assumptions, values, principles, ideologies, paradigms and valued ends that inform our practice. An approach for intellectual showcasing is offered that may serve as an accountability identifier for the public and us.